Setting up your first sales team with with Patrick Traynor (Assemble You, 2023)
In this episode of the Power Skills Project, Adam is joined by sales guru, Pat Traynor. Pat has been building and leading B2B sales teams for over 15 years, with particular experience in early-stage startups. He's been the first sales hire or first sales leader on eight occasions, including becoming LinkedIn's first sales hire outside the US. Since 2015 Pat's joined several advisory boards, invested in a dozen UK startups, and through his consultancy firm, Silicon Growth, supports startup founders with sales strategy, design and execution as they build out their sales organisations. This interview is perfect if you have a direct-to-consumer product and are thinking of going into business sales or, perhaps, you are a founder doing sales and need to expand your sales function. Or maybe you have fallen into a sales management position and just need a bit more structure and guidance. In it, Pat takes us through some of the frameworks he applies when helping clients develop a sales team, including four steps on where to start, followed by People, Product, Process and Tech, and finally, Strategy, Operations and Enablement.